2022
DOI: 10.1029/2021jd036270
|View full text |Cite
|
Sign up to set email alerts
|

Gravity‐Wave‐Driven Seasonal Variability of Temperature Differences Between ECMWF IFS and Rayleigh Lidar Measurements in the Lee of the Southern Andes

Abstract: Long‐term high‐resolution temperature data of the Compact Rayleigh Autonomous Lidar (CORAL) is used to evaluate temperature and gravity wave (GW) activity in ECMWF Integrated Forecasting System (IFS) over Río Grande (53.79°S, 67.75°W), which is a hot spot of stratospheric GWs in winter. Seasonal and altitudinal variations of the temperature differences between the IFS and lidar are studied for 2018 with a uniform IFS version. Moreover, interannual variations are considered taking into account updated IFS versi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…As expected, the horizontal extent of concentric GWs expands as the waves propagate upward, consistent with the CIPS and AIRS observations shown in Figures 2a and 2b. Amplitudes of concentric waves are getting weaker above 0.8 hPa level (∼55 km) and wave structures are significantly weakened and disappeared above 0.25 hPa level (∼60 km), which we believe is due to damping in ECMWF at higher altitudes by the sponge layers discussed by previous studies (e.g., Ehard et al., 2018; Gisinger et al., 2022). Gisinger et al.…”
Section: Results Of Typhoon Yutu Generated Gravity Wavessupporting
confidence: 47%
See 2 more Smart Citations
“…As expected, the horizontal extent of concentric GWs expands as the waves propagate upward, consistent with the CIPS and AIRS observations shown in Figures 2a and 2b. Amplitudes of concentric waves are getting weaker above 0.8 hPa level (∼55 km) and wave structures are significantly weakened and disappeared above 0.25 hPa level (∼60 km), which we believe is due to damping in ECMWF at higher altitudes by the sponge layers discussed by previous studies (e.g., Ehard et al., 2018; Gisinger et al., 2022). Gisinger et al.…”
Section: Results Of Typhoon Yutu Generated Gravity Wavessupporting
confidence: 47%
“…Amplitudes of concentric waves are getting weaker above 0.8 hPa level (∼55 km) and wave structures are significantly weakened and disappeared above 0.25 hPa level (∼60 km), which we believe is due to damping in ECMWF at higher altitudes by the sponge layers discussed by previous studies (e.g., Ehard et al, 2018;Gisinger et al, 2022). Gisinger et al (2022) observed that above ∼45 km the amplitudes of GWs in ECMWF are weaker than in lidar observations. Although GW amplitudes might be reduced above ∼45 km, our results indicate that GW structures are reasonably simulated compared to CIPS around 50-55 km.…”
Section: Results Of Typhoon Yutu Generated Gravity Wavesmentioning
confidence: 41%
See 1 more Smart Citation
“…Note that the major phase lines in the IFS data are aligned in an almost identical orientation compared with the airborne observations. A lower degree of agreement of the amplitudes of Δ T above 40 km is probably related to increased layer level spacing and artificial damping in the IFS model (e.g., Gisinger et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The scientific objectives were very diverse, ranging from examining air polluted by biomass burning in the tropics (Johansson et al, 2022) (and, as a target of opportunity, Australia; Ohneiser et al, 2022), the breakdown of the Antarctic polar vortex and the associated chemical and physical structure, the general chemical composition of the Southern Hemisphere's upper troposphere-lower stratosphere (Johansson et al, 2022), to studying gravity waves. Some exemplary outcomes from the gravity wave part of the SouthTRAC campaign include clear-air turbulence studies (Rodriguez Imazio et al, 2022;Dörnbrack et al, 2022), gravity wave propagation from the Southern Andes and the Antarctic peninsula into the mesosphere (Reichert et al, 2021;Conte et al, 2022), gravity wave observation and model intercomparison (Gisinger et al, 2022;Dörnbrack et al, 2022;Liu et al, 2022;Alexander et al, 2022), mountain waves drifting upwind of the Andes (Krasauskas et al, 2022), gravity wave refraction due to wind shear (Geldenhuys et al, 2022), and gravity waves from orographic and non-orographic sources (Alexander et al, 2022;de la Torre et al, 2022).…”
Section: Flight Planning For the Southtrac Campaignmentioning
confidence: 99%